Comparison of neutrophil extracellular trap induction and reactive oxygen species production between non-capsulated and capsulated strains of burkholderia Thailandensis - Donporn Riyapa (2020)
© 2019, SEAMEO TROPMED Network. All rights reserved. Polymorphonuclear neutrophils (PMNs) play a role in host defense by eliminating infectious pathogens through phagocytic activity and degranulation. Neutrophil extracellular traps (NETs) are an additional antimicrobial mechanism of PMNs that involve releasing nuclear DNA and antimicrobial proteins to entrap and kill microbes. The generation of NETs requires reactive oxygen species (ROS) production via the activation of NADPH oxidase complex with certain NET-inducing stimuli. However, little is known about Burkholderia thailandensis-induced NETs. In this study, we aimed to compare NET formation and ROS levels between typical B. thailandensis strain E264 (non-capsulated strain) and a variant B. thailandensis strain E555 (capsulated strain). B. thailandensis strain E555 was included in this study due to its production of a capsule similar to the pathogenic bacteria Burkholderia pseudomallei. We performed this comparison to determine if the capsule would result in a difference in NET formation. The amounts of NETs were measured using a fluorometric double-stranded DNA quantification assay and the ROS levels were measured by flow cytometry. At a multiplicity of infection (MOI) of 10, B. thailandensis strain E555 induced significantly less (193.0 ng/ml) NET formation than B. thailandensis strain E264 (285.4 ng/ml, p<0.05). Significantly lower ROS levels were produced by B. thailandensis strain E555 (MFI value 37.6) than B. thailandensis strain E264 (MFI value 63.4, p<0.05). Our results showed both strains of B. thailandensis induced NET formation and ROS levels. However, strain E555 induced less NET formation and produced lower ROS levels than strain E264, suggesting the capsule enabled B. thailandensis strain E555 to evade the induction and killing activity of NETs. Further studies are needed to determine if these differences are due to the capsule or other factors.